Identification and characterization of the GH3 gene family in maize - ZHANG, Dong-feng; ZHANG, Nan; ZHONG, Tao; WANG, Chao; XU, Ming-liang; YE, Jian-rong (Journal of Integrative Agriculture, 2016)
The phytohormone auxin plays a central role in coordinating plant growth and development.GH3 is one of the three gene families that respond rapidly during auxin stimulation.Here,we report the identification and characterization of the GH3 gene family in maize.A total of 12 GH3 genes were identified,which are not evenly distributed over the 10 maize chromosomes.Maize GH3 protein sequences share a conserved domain which occupies nearly the entire protein.Diversified c/＇s-elements were found in promoters of maize GH3 genes.In this study,the 12 maize GH3 proteins were primarily classified into two phylogenetic groups,similar to the 13 rice GH3 proteins,while 9 of the 19 Arabidopsis GH3 proteins were observed in the third phylogenetic group.Microarray analysis showed that expression of maize GH3 genes is temporally and spatially modulated.Additionally,maize GH3 genes displayed variable changes at transcript level upon pathogen infection.Results presented here provide insight into the diversification and evolution of GH3 proteins,and lay a foundation for the functional characterization of these GH3 genes in future,especially for elucidating the mechanisms of GH3-mediated pathogenesis.